2017
DOI: 10.1016/j.crvasa.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Novel pulmonary artery banding followed by transcatheter balloon dilatation in treatment of complex congenital heart defects

Abstract: Tento článek prosím citujte takto: L. Vazquez-Garcia, et al., Novel pulmonary artery banding followed by transcatheter balloon dilatation in treatment of complex congenital heart defects, Cor et Vasa 59 (2017) e465-e467, jak vyšel v Cor et Vasa na

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Dacron 1 may be too solid to allow balloon debanding with a large size balloon, and attempts may be complicated by tearing of the pulmonary arterial wall unless the suture threads do not break. Vazquez-Garcia et al reported debanding for ePTFE band using a balloon 1.2-2.0 times to the narrowest segment of pulmonary artery [6]. In their report, a small but a significant pressure gradient remained after balloon debanding.…”
Section: Discussionmentioning
confidence: 95%
“…Dacron 1 may be too solid to allow balloon debanding with a large size balloon, and attempts may be complicated by tearing of the pulmonary arterial wall unless the suture threads do not break. Vazquez-Garcia et al reported debanding for ePTFE band using a balloon 1.2-2.0 times to the narrowest segment of pulmonary artery [6]. In their report, a small but a significant pressure gradient remained after balloon debanding.…”
Section: Discussionmentioning
confidence: 95%